2023
DOI: 10.3233/jad-230207
|View full text |Cite
|
Sign up to set email alerts
|

Race and Ethnicity in Lewy Body Dementia: A Narrative Review

Abstract: Lewy body dementia is the third most common and costliest type of dementia. It is an umbrella term for dementia with Lewy bodies and Parkinson’s disease dementia, both of which place a substantial burden on the person and society. Recent findings outline ethnoracial differences in dementia risk. Delayed and misdiagnosis across ethnoracial groups contribute to higher levels of burden. In this context, we aimed to summarize current knowledge, gaps, and unmet needs relating to race and ethnicity in Lewy body deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Another limitation of this study is the lack of racial and ethnic diversity, with only one non-White donor in the current cohort. It is important to recognise that the recruitment of non-White tissue donors needs to improve, in order to investigate the reasons for observed differences in the presentation ( Kurasz et al, 2020 ) and diagnosis ( Kurasz et al, 2022 ; Bayram et al, 2023 ) of LBDs that have been noted in different racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is the lack of racial and ethnic diversity, with only one non-White donor in the current cohort. It is important to recognise that the recruitment of non-White tissue donors needs to improve, in order to investigate the reasons for observed differences in the presentation ( Kurasz et al, 2020 ) and diagnosis ( Kurasz et al, 2022 ; Bayram et al, 2023 ) of LBDs that have been noted in different racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most findings stem from studies including people identifying as non‐Hispanic White with higher levels of education and more access to resources, the generalizability and applicability of these findings remains questionable. For instance, significant sex and gender differences for the prevalence and impact of underlying Lewy body pathology, 29 and potentially lower diagnostic accuracy in people from minoritized ethnoracial groups 33 need to be better understood. As efforts focus on harmonizing data from cohorts in different centers and countries, 16 outreach to and inclusion of underrepresented communities also needs to be emphasized to support diagnostic and therapeutic advances in DLB.…”
Section: The Current and Future State Of Lewy Body Dementiamentioning
confidence: 99%
“…Multiple studies using the U.S.-based National Alzheimer Coordinating Center (NACC) database identified that fewer Black participants with pathologic Lewy body disease had a clinical suspicion for Lewy body dementia in life compared to White or Hispanic participants [ 5, 6 ]. Over 96% of participants in clinical trials for Lewy body dementia identify as White [ 7 ].…”
Section: Introductionmentioning
confidence: 99%